Bagpipes, brides and homicides - Dunnett, Kaitlyn (Dunnett, Kaitlyn. Liss MacCrimmon mystery., 2012)
Moosetookalook, Maine, has never seen so many bare legs walking its streets. It could only mean one thing: the Western Maine Highland Games are in town for the weekend. But instead of wondering who'll win the hammer throw, everyone's asking who got kilt. . .Even if Liss MacCrimmon, soon to be Mrs. Dan Ruskin, spends her days running the Moosetookalook Scottish Emporium, all she wants is a simple white wedding as she walks down the aisle accompanied by her father. When it comes to weddings, however, her mother, Vi, has another idea about tradition. Instead of white, Vi sees tartan, tartan, and more tartan. What bonnie luck then that Liss and Dan's wedding is scheduled on the same weekend as the Western Maine Highland Games. What could make a nuptial weekend more memorable than a hammer throw or medieval reenactment group to go along with the tossing of the bouquet? How about a charming college professor found slashed to death by his own reproduction of a broadsword? But who'd go medieval on a professor, no matter how nutty? Turns out the deceased had plenty of enemies, including a line of female conquests stretching back to the dark ages, a band of picketers protesting his historically questionable theories, and a strapping collegiate with a howdy-doody smile. And topping the suspect list is Liss's own father, Donald "Mac" MacCrimmon! As much as Liss tries to keep her fingers out of the sleuthing cake, she finds herself again dead center of a Moosetookalook murder mystery. If Liss doesn't solve this one, and quick, she might never say "I do," let alone" 'til death do us part."